2013
DOI: 10.1016/j.ccr.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The RasGAP Gene, RASAL2, Is a Tumor and Metastasis Suppressor

Abstract: SUMMARY RAS genes are commonly mutated in cancer; however, RAS mutations are rare in breast cancer, despite the fact that Ras and ERK are frequently hyperactivated. Here we report that the RasGAP gene, RASAL2, functions as a tumor and metastasis suppressor. RASAL2 is mutated or suppressed in human breast cancer and RASAL2 ablation promotes tumor growth, progression, and metastasis in mouse models. In human breast cancer RASAL2-loss is associated with metastatic disease, low RASAL2 levels correlate with recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
130
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 43 publications
9
130
1
Order By: Relevance
“…EMT in mammary epithelial cells typically facilitates tumor cell migration and invasion (27). Previously, RASAL2 was identified as a mediator of EMT and metastasis in ovarian cancer, lung adenocarcinoma and breast cancer (14)(15)(16). In the present study, RASAL2 was demonstrated to be a mediator of EMT, migration and invasion in CRC cells.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…EMT in mammary epithelial cells typically facilitates tumor cell migration and invasion (27). Previously, RASAL2 was identified as a mediator of EMT and metastasis in ovarian cancer, lung adenocarcinoma and breast cancer (14)(15)(16). In the present study, RASAL2 was demonstrated to be a mediator of EMT, migration and invasion in CRC cells.…”
Section: Discussionmentioning
confidence: 58%
“…Mutations in RAS genes frequently lead to permanently activated RAS and thus its downstream effectors, which causes aberrant cell proliferation and potential tumorigenesis (14). Previous studies have demonstrated that mutation of RAS genes is the primary mechanism of aberrant RAS activation (8,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45 RASAL2, a closely related member in the RASAL1 family, has also been shown to suppress tumorigenicity and metastasis. 46 This general characteristic of RASAL genes needs further investigation to obtain confirmation.…”
Section: Discussionmentioning
confidence: 99%